Influence of weight at the time of first palliation on survival in patients with a single ventricle. (27th June 2017) - Surendran, Sushitha; Kumar, T. K. Susheel; Tansey, Ben; Allen, Jerry; Zurakowski, David; Boston, Umar; Shah, Samir H.; Knott-Craig, Christopher J.
Abstract: Background: Numerous advances in surgical techniques and understanding of single-ventricle physiology have resulted in improved survival. We sought to determine the influence of various demographic, perioperative, and patient-specific factors on the survival of single-ventricle patients following stage 1 palliation at our institution. Methods: We conducted a retrospective study of all single-ventricle patients who had undergone staged palliation at our institution over an 8-year period. Data were collected from the Society of Thoracic Surgeons Congenital Heart Surgery database and from patient charts. Information on age, weight at stage 1 palliation, prematurity, genetic abnormalities, non-cardiac anomalies, ventricular dominance, and type of palliation was collected. Information on mortality and unplanned reinterventions was also collected. Results: A total of 72 patients underwent stage 1 palliation over an 8-year period. There were 12 deaths before and one death after stage 2 palliation. There was no hospital mortality following Glenn or Fontan procedures. On univariate analysis, low weight at the time of stage 1 palliation and prematurity were found to be risk factors for mortality following stage 1 palliation. However, multivariable Cox regression analysis revealed weight at stage 1 palliation to be a strong predictor of mortality. The type of stage 1 palliation did not have any influence on the outcome. No difference in survival was noted following the Glenn procedure. Conclusion: Low weight has a deleterious impact on survival following stage 1 palliation. This is mitigated by stage 2 palliation. The type of stage 1 palliation itself has no bearing on the outcome.